A higher tumor volume and undernutrition at diagnosis adversely affect the survival of children with Wilms tumor: A study of 200 patients. Issue 11 (16th July 2022) - Rahiman, Emine A; Trehan, Amita; Jain, Richa; Menon, Prema; Kakkar, Nandita; Srinivasan, Radhika; Sodhi, Kushaljit Singh; Saxena, Akshay Kumar; Kapoor, Rakesh; Bansal, Deepak
Abstract: Background: Distinct prognostic factors for Wilms tumor (WT) in low‐ and middle‐income countries need identification. Methods: Retrospective study of patients with WT managed by the International Society of Pediatric Oncology (SIOP) approach for over 11 years (2005–2016) at a single center in Chandigarh, India. Results: The study included 200 patients (median age: 33.5 months). The tumor stage (SIOP) distribution included stage I (30%), II (36%), III (14%), IV (17%), and V (3%). The histology‐risk groups were low (8%), intermediate (84%), and high risk (9%). At diagnosis, 68 out of 190 (36%) patients were underweight. The median tumor volume at diagnosis was 481 ml (interquartile ratio [IQR]: 306.9, 686.8, n = 146). Following neoadjuvant chemotherapy, it reduced to 110 ml (IQR: 151.2, 222, n = 77). Treatment was abandoned in 20.5% of the patients. Treatment‐related mortality occurred in 13 of 179 (7.2%) patients. Relapse occurred in 26 of 158 (16.5%) patients. The 3‐year overall survival (OS) and event‐free survival (EFS) of patients who completed therapy were 78.3 and 72%, respectively. The stage ( p = .013) and histology ( p = .023) influenced OS. A lower OS in stage II (75.4%) versus stage III disease (83.7%) suggested understaging. Patients with a higher tumor volume at diagnosis ( p = .005; odds ratio [OR]: 0.99; 95% confidence interval [CI]: 0.99–1.00) or a lower weight‐for‐age z ‐score ( p = .002; OR: 1.68; 95% CI: 1.21–2.33) had an increased risk of death or relapse. Conclusions: The 3‐year OS and EFS of children who completed therapy were 78.3 and 72%, respectively. A higher tumor volume and lower weight‐for‐age z ‐score at diagnosis were identified as distinct adverse prognostic factors. A likely suboptimal lymph node assessment (intraoperative and histopathology) contributed to the understaging of stage III to II disease and reduced survival.